Behold the Buddha : Religious meanings of Japanese Buddhist icons - Dobbins, James C. (University of Hawai'i Press, 2020)
Behold the Buddha is a clear, concise, and compellingly written guide to the visual culture and iconography of Japanese Buddhism, supplemented with beautiful illustrations. Author James C. Dobbins expertly decodes the complex mysteries behind Buddhist masters, relics, and calligraphy, equipping readers with an intellectual approach to engage with and understand these images as art and symbols for Buddhist teachings and ritual.